2017
DOI: 10.1016/s2468-2667(17)30072-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rapid privatisation on mortality in mono-industrial towns in post-Soviet Russia: a retrospective cohort study

Abstract: SummaryBackgroundPopulation-level data suggest that economic disruptions in the early 1990s increased working-age male mortality in post-Soviet countries. This study uses individual-level data, using an indirect estimation method, to test the hypothesis that fast privatisation increased mortality in Russia.MethodsIn this retrospective cohort study, we surveyed surviving relatives of individuals who lived through the post-communist transition to retrieve demographic and socioeconomic characteristics of their pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…However, using multilevel data on settlements and individuals we have confirmed that privatisation was associated with higher mortality among men in Russia (Azarova et al . ), and among women in Hungary (Scheiring et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, using multilevel data on settlements and individuals we have confirmed that privatisation was associated with higher mortality among men in Russia (Azarova et al . ), and among women in Hungary (Scheiring et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers questioned the robustness of the association between shock therapy and mortality arguing that the result was prone to ecological fallacy (Gentile 2012;Earle and Gehlbach 2010). A recently published article has shown that the association between mass privatisation and mortality was real, confirming the detrimental health effect of rapid privatisation using multilevel individual, company and settlement data (Azarova et al 2017).…”
Section: Discussion: the Hungarian Literature In The Post-socialist Cmentioning
confidence: 99%
“…There is accumulating evidence of the ways in which consequences of sudden economic transformations such as increasing precariousness of employment (Barlow et al 2015), work (Waters 2014) and housing (Clair et al 2016) impact adversely on health. Neoliberal policies have been empirically shown to increase health problems and mortality (Coburn 2000;De Vogli 2011), including the detrimental health effect of rapid privatisation (Azarova et al 2017), structural adjustment (Kentikelenis 2017), or austerity (Karanikolos et al 2013).…”
Section: Discussion: the Hungarian Literature In The Post-socialist Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet after some four decades’ experience with neoliberal policies, even IMF economists have recognized that neoliberalism's “benefits in terms of increased growth seem fairly difficult to establish,” while its “costs in terms of increased inequality are prominent” (Ostry, Loungani, & Furceri , p. 39). The natural experiment provided by the former Soviet Union indicates that neoliberal economic policies contribute to greater anomie and crime (Passas, ), along with an increase in premature deaths (Azarova et al., ). Global rates of economic growth have been lower in the neoliberal era, compared to those of the decades of “collectivist” planning and restrictions on finance and trade (Chang, ; Harvey ).…”
Section: Where the Road To Neoliberalism Has Ledmentioning
confidence: 99%